Ciliary Neurotrophic Factor Acts on Distinctive Hypothalamic Arcuate Neurons and Promotes Leptin Entry Into and Action on the Mouse Hypothalamus - Venema, Wiebe; Severi, Ilenia; Perugini, Jessica; Di Mercurio, Eleonora; Mainardi, Marco; Maffei, Margherita; Cinti, Saverio; Giordano, Antonio (Frontiers in Cellular Neuroscience, 2020)
In humans and in experimental animals, administration of ciliary neurotrophic factor (CNTF) reduces food intake and body weight. To gain further insights into the mechanism(s) underlying its satiety effect, we i) evaluated the CNTF-dependent activation of the Janus kinase 2 (JAK2) and signal transducer and activator of transcription 3 (STAT3) pathway in mouse models where neuropeptide Y (NPY) and pro-opiomelanocortin (POMC) neurons can be identified by green fluorescent protein (GFP), and ii) assessed whether CNTF promotes leptin signaling in hypothalamic feeding centers. Immunohistochemical experiments enabled us to establish that intraperitoneal injection of mouse recombinant CNTF activated the JAK2-STAT3 pathway in a substantial proportion of arcuate nucleus (ARC) NPY neurons (18.68% + 0.60 in 24-hour fasted mice and 25.50% + 1.17 in fed mice) but exerted a limited effect on POMC neurons (4.15% + 0.33 in 24-hour fasted mice and 2.84 % + 0.45 in fed mice). CNTF-responsive NPY neurons resided in the ventromedial ARC, facing the median eminence (ME), and were surrounded by albumin immunoreactivity, suggesting that they are located outside the blood-brain barrier. In both normally fed and high-fat diet (HFD) obese animals, CNTF activated extracellular signal-regulated kinase signaling in ME β1- and β2-tanycytes, an effect that has been linked to promotion of leptin entry into the brain. Accordingly, compared to the animals treated with leptin, mice treated with leptin/CNTF showed: i) a significantly greater leptin content in hypothalamic protein extracts; ii) a significant increase in P-STAT3-positive neurons in the ARC and the ventromedial hypothalamic nucleus of normally fed mice; and iii) a significantly increased number of P-STAT3-positive neurons in the ARC and dorsomedial hypothalamic nucleus of HFD obese mice. Collectively, these data suggest that exogenously administered CNTF reduces food intake by exerting a leptin-like action on distinctive NPY ARC neurons and by promoting leptin signaling in hypothalamic feeding centers.